CoNi2S4 nanoparticle on carbon cloth with high mass loading as multifunctional electrode for hybrid supercapacitor and overall water splitting - Ye, Jing; Li, Qi; Ma, Xiao; Chen, Huizhen; Yuan, Tingting; Xu, Xuetang; Wang, Fan (Applied surface science, 2021)
[Display omitted] •CoNi2S4 nanoparticles with high mass loading (15 mg cm−2) grown on carbon cloth.•High capacitance of 10.87F cm−2 at 10 mA cm−2 and a prominent coulombic efficiency.•All-solid-state hybrid supercapacitor delivers 1.42 mWh cm−2 at 9.0 mW cm−2.•Excellent HER (84 mV at 10 mA cm−2) and OER (228 mV at 10 mA cm−2) activities. Transition-metal sulfides are regarded as one of the most potential materials for the supercapacitor and electrocatalyst, and the holey alignments of the active materials with effective availability is highly required due to the rich active sites and convenient electrolyte access for surface reaction. Herein, we report the growth of CoNi2S4 nanoparticles with high mass loading (14.8 mg cm−2) on the surface of carbon cloth (CC) by a two-step hydrothermal sulfuration. The CoNi2S4/CC electrode has the holey characteristic containing rich active sites for electrolyte access, and shows a high areal capacitance of 10.87 C cm−2 at 10 mA cm−2 and a prominent coulombic efficiency. Furthermore, the as-assembled hybrid supercapacitor delivers a high areal capacitance of 3.16 F cm−2, an energy density of 1.42 mWh cm−2 at a power density of 9.0 mW cm−2, and a high capacitance retention of 92.5% after 20,000 cycles. As an electrocatalyst, CoNi2S4/CC electrode possesses an excellent hydrogen evolution reaction (overpotential of 84 mV at 10 mA cm−2) and oxygen evolution reaction (228 mV at 10 mA cm−2) activities in 1.0 M KOH solution. Moreover, the overall water splitting electrolyzer assembled by CoNi2S4/CC exhibits a low cell voltage (1.51 V@10 mA cm−2) and a high durability.